Serum osmolality and effects of water deprivation in captive Asian elephants (Elephas maximus) - Hall, Natalie H. (2012)
Serum from 21 healthy, captive Asian elephants (Elephas maximus) was evaluated by measured and calculated osmolality. Serum osmolality results for this population of Asian elephants had a median of 261 mOsm/kg and an interquartile interval of 258–269 mOsm/kg when measured by freezing point osmometry and a median of 264 mOsm/kg and an interquartile interval of 257–269 mOsm/kg when measured by vapor pressure osmometry. These values are significantly lower than values reported in other mammalian species and have important diagnostic and therapeutic implications. Calculated osmolality produced unreliable results and needs further study to determine an appropriate formula and its clinical application in this species. A 16-hr water deprivation test in 16 Asian elephants induced a small, subclinical, but statistically significant increase in measured serum osmolality. Serum osmolality, blood urea nitrogen, and total protein by refractometer were sensitive indicators of hydration status. Serum osmolality measurement by freezing point or vapor pressure osmometry is a useful adjunct to routine clinical tests in the diagnostic evaluation of elephants.